2015
DOI: 10.1038/ncomms7147
|View full text |Cite
|
Sign up to set email alerts
|

Formation of titanium monoxide (001) single-crystalline thin film induced by ion bombardment of titanium dioxide (110)

Abstract: A plethora of technological applications justify why titanium dioxide is probably the most studied oxide, and an optimal exploitation of its properties quite frequently requires a controlled modification of the surface. Low-energy ion bombardment is one of the most extended techniques for this purpose and has been recently used in titanium oxides, among other applications, to favour resistive switching mechanisms or to form transparent conductive layers. Surfaces modified in this way are frequently described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 33 publications
(35 reference statements)
5
36
0
Order By: Relevance
“…Through the quantitative analysis of EELS results, 28 it was found that, as shown in Fig. S2, the oxygen content in the film is not uniform and the averaged O/Ti ratio is about 1.11-1.25, which is similar to that reported by Pabon et al 20 Although the combination of STEM images with electron diffraction pattern is a powerful tool in determining the crystal structure of materials, the results provide only local structural information of a small volume. Therefore, we carried out detailed XRD experiments.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Through the quantitative analysis of EELS results, 28 it was found that, as shown in Fig. S2, the oxygen content in the film is not uniform and the averaged O/Ti ratio is about 1.11-1.25, which is similar to that reported by Pabon et al 20 Although the combination of STEM images with electron diffraction pattern is a powerful tool in determining the crystal structure of materials, the results provide only local structural information of a small volume. Therefore, we carried out detailed XRD experiments.…”
Section: Resultssupporting
confidence: 76%
“…One of the reasons for the difference in lattice parameters between the TiO film and the bulk may be related to the oxygen content, because it was reported that the lattice parameter could be reduced with increasing oxygen content. 7,19,20 As shown in the inset of The existence of the superconducting phase in the TiO film was unambiguously confirmed by its Meissner effect and zero resistance. Figure 2a shows the direct-current (DC) magnetizations vs. temperature (M-T) of the TiO film.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Oxide surfaces are prone to the formation of oxygen vacancies [64][65][66] and as discussed above, we also observe the presence of oxygen vacancies at the surface of the superlattice film from O K edge EELS.…”
Section: Suppression Of Peak a And Change In Separation Between The supporting
confidence: 77%
“…Rapid quenching from high temperature is especially required to avoid the γ–α phase transformation . Nanocrystalline TiO has been successfully prepared by nonconventional methods, such as laser pyrolysis, laser ablation, low‐energy ion bombardment technique, and mechanochemical synthesis by using high‐energy ball milling and subsequent annealing . Unfortunately, these fabrication routes have encountered with contamination problem and harsh synthesis conditions induced difficulty in nanostructure construction.…”
mentioning
confidence: 99%